Urgensi Bimbingan Pra Nikah bagi Calon Pasangan Pengantin di KUA Kota Salatiga - Nastangin Nastangin (Universitas Wahid Hasyim Semarang, 2021)
Pre-marital guidance is a process of social service in the form of counseling, service provided to husband and wife before carrying out marriage so that they obtain prosperity and happiness in marriage and family life. The phenomenon takes serious attention, accordingly there must be some effort to overcome it, one of the ways is through the application of pre-marital guidance. For this theme, the researcher takes qualitative research to understand the phenomena about what is experienced by research subjects such as behavior, perception, motivation, actions and others, holistically, and in a descriptive way in the form of words and language, especially by utilizing various natural methods in field research. The findings of this research shows the implementation process of pre-marital guidance in religious Affairs office (KUA) of Salatiga City has not been scheduled routinely in most cases. There are 2 forms of pre-marital guidance: first, pre-marital guidance holding at center of religious Affairs office, second, independent pre-marital guidance holding by each religious Affairs office (KUA) in sub-district. In the implementation of pre-marital guidance holding by the religious Affairs office of Salatiga City has several problems namely there are time problems, funds / budget, facilities and infrastructure. The impact of pre-marital guidance in stabilizing the bride and groom to realize a sakinah family in KUA Salatiga City is the preparation of the bride and groom before attending pre-marital guidance. the fact is the bride and groom do not know about the duties of a husband and wife, rights and obligations husband and wife, how to overcome problems in the family and the solution to minimize fight in the family and to minimize the occurrence of divorce.